Performance Effectiveness of the Village Financial Affairs Officer in Village Financial Management in Parungkokosan Village, Cikeusik District, Pandeglang Regency - Ahmad Mufarrihum; Nasir Nasir; Saryani Saryani (ijd-demos, 2025)
This study aims to examine and analyze the performance effectiveness of the Village Financial Affairs Officer in managing the finances of Parungkokosan Village, Cikeusik District, Pandeglang Regency. Village financial management is a crucial aspect of village governance, as it encompasses the planning, implementation, administration, reporting, and accountability regarding the use of the village budget—processes that must be carried out transparently, accountably, effectively, and in compliance with applicable regulations. This study employs a qualitative research method with a descriptive approach. Data collection techniques included observation, interviews, and documentation. The results indicate that the performance effectiveness of the Village Financial Affairs Officer in managing Parungkokosan Village's finances has generally been quite effective. This is evident from the execution of tasks related to financial administration, report preparation, and financial accountability, all of which have been carried out in accordance with prevailing regulations. Based on Richard M. Steers' perspective, the goal achievement indicator shows that the officer's performance has supported the attainment of village financial management objectives. Regarding the integration indicator, coordination and communication between the Financial Affairs Officer and other village government officials have effectively supported task execution. Meanwhile, concerning the adaptation indicator, the Village Financial Affairs Officer has demonstrated the ability to adjust to changes in regulations and village financial administration systems. Keywords: Performance Effectiveness, Village Financial Affairs Officer, Village Financial Management, Village Governance.